2011
DOI: 10.1371/journal.pone.0017093
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium indicus pranii Supernatant Induces Apoptotic Cell Death in Mouse Peritoneal Macrophages In Vitro

Abstract: Mycobacterium indicus pranii (MIP), also known as Mw, is a saprophytic, non-pathogenic strain of Mycobacterium and is commercially available as a heat-killed vaccine for leprosy and recently tuberculosis (TB) as part of MDT. In this study we provide evidence that cell-free supernatant collected from original MIP suspension induces rapid and enhanced apoptosis in mouse peritoneal macrophages in vitro. It is demonstrated that the MIP cell-free supernatant induced apoptosis is mitochondria-mediated and caspase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
2
8
1
Order By: Relevance
“…Experimental results imply MIP HKB selectivity in MDA-MB-231, MCF-7, CaSki, A549, SK-LU-1, DU-145, HepG2, ORL-48, ORL-115 and ORL-136 with IC 50 values between 5.6 to 21 μl/(1.0 × 10 6 MIP cells/ml), all of which are lower than non-cancerous cells. According to a previous study on apoptotic cell death in in vitro by Pandey et al , 2011 15 , 60–70 μl of MIP is required to induce cell death in 40–45% mouse peritoneal macrophages while in this study, 60–70 μl/(1.0 × 10 6 MIP cells/ml) of MIP HKB induced 75% cell death. This clearly shows a tremendous reduction in MIP dose when a 60 °C heat kill technique was applied compared to autoclave heat kill technique.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Experimental results imply MIP HKB selectivity in MDA-MB-231, MCF-7, CaSki, A549, SK-LU-1, DU-145, HepG2, ORL-48, ORL-115 and ORL-136 with IC 50 values between 5.6 to 21 μl/(1.0 × 10 6 MIP cells/ml), all of which are lower than non-cancerous cells. According to a previous study on apoptotic cell death in in vitro by Pandey et al , 2011 15 , 60–70 μl of MIP is required to induce cell death in 40–45% mouse peritoneal macrophages while in this study, 60–70 μl/(1.0 × 10 6 MIP cells/ml) of MIP HKB induced 75% cell death. This clearly shows a tremendous reduction in MIP dose when a 60 °C heat kill technique was applied compared to autoclave heat kill technique.…”
Section: Discussionsupporting
confidence: 42%
“…In cancer treatment, MIP is used as an adjuvant to radiation therapy in patients with bladder cancer 12 and to chemotherapy plus radiotherapy in non-small cell lung cancers 10 . Four types of fractions can be obtained from MIP: LB, HKB, CS and HKS, with the most widely used fractions being the HKB fraction 13 14 and CS fraction 15 . While past studies have cited autoclaving for 20 mins at 15 lb/in 2 as the most common heat killing method, this method may denature important and biologically active proteins, which led us to heat-kill MIP at 60 °C, which was also found to be sufficient in killing MIP cultures.…”
Section: Discussionmentioning
confidence: 99%
“…47 However, inhibition of PKCd with rottlerin abrogated apoptosis in murine macrophages when cultured with cell-free supernatant of Mycobacterium indicus pranni (Mw). 48 In contrast, we observed increased apoptosis in PKCd À / À macrophages following Mtb infection. This observation strengthens accumulating evidence regarding the nonspecific actions of rottlerin as a PKCd inhibitor.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous study has demonstrated that MIP could induce mitochondria-mediated apoptosis in mouse peritoneal macrophages in vitro. 28 Thus, in this study we have tested intrinsic apoptotic protein expression in MIP combinations using Apaf-1 and caspase-9 to validate intrinsic apoptosis-mediated cell death. As shown in Figure 2 , caspase-9 cleavage products were observed in increasing concentrations, while procaspase-9 was reduced upon treatment with the two drugs and agent combinations at 6 hours in MCF-7.…”
Section: Resultsmentioning
confidence: 99%